Audit committee chair effectiveness and firm performance: The mediating role of sustainability disclosure - Ahmad Yuosef Alodat; Hamzeh Al Amosh; Saleh F. A. Khatib; Marwan Mansour (Cogent Business & Management, 2023)
The primary goal of this study is to investigate the influence of sustainability disclosure (SD) practices on the relationship between audit committee chair characteristics and firms' performance. The current study used an experimental approach to data collection and analysis. The predicted variable is the AC chair characteristics; the predictor variables are the performance indicator's return on equity (ROE). The study investigated the indirect impact of the mediating role in the SD index. We manually analysed 405 annual reports of the companies listed on the ASE from 2014 to 2018. The findings revealed a significant and positive relationship between the accounting expertise, tenure, and monitoring expertise of the AC chairs and the performance of the firm measures tested, namely, ROA and ROE. Meanwhile, AC chair experiential expertise types and firm performance measures have a positive but insignificant relationship. Furthermore, the findings revealed that sustainability disclosure mediates the relationship between AC chair effectiveness and ROE in part. The results of this study will help firms understand the expertise of AC chair characteristics that can help firms in Jordan to perform better. The findings indicated that the effectiveness of AC chairs contributes to improved firm performance through sustainability practices. This study is one of the few studies that dealt with AC chair characteristics and one of the first studies that linked this variable to firm performance. Furthermore, our selection of the Jordanian context emphasizes the topic's importance, as it is one of the developing contexts that has recently seen regulatory reforms in financial markets. It also expands on previous research by looking at Jordan's listed ASE firms.
Keywords: 650; audit committee chair characteristics; firm performance; sustainability disclosure